Abandoned and Haunted: the Imaginary of the Hotel between Old and New Stories - Piluso, Francesco (E|C, 2022)
The hospitality industry has been going through a deep crisis in these last few years. Nevertheless, many hotels have been experimenting with new ways to attract clients and guests in such a difficult period. More and more hotels are establishing themselves as protagonists of their own stories or as places of historical importance. In contrast to their state of neglect and abandon, this strategy is implemented by many hotels to renew a value coming from the past, make it present or even haunting presence. The aim of this essay is to investigate the role and the capacity of the hotel to create and benefit from a series of narrative images, trying to point out recurring themes and figures, analyzing their modalities of media circulation and understanding the reasons of a renovated public success.